Librarians Working with Publishers on E-book Provision - Loarer, Pierre Le; Salaün, Jean-Michel (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
The traditional library builds a world of limited knowledge for a limited number of people: the economy of the traditional library is based on the service for an identified community of people. This community is limited and, in most cases, the external patrons are very few. The justifications of a library are mutualisation of the costs (an item for several patrons), opportunities of reading (discovery of documents by the effect-collection, „ just in time” ) and insurance (preserving the access „ just in case” ). Thus, the representatives of the communities they are serving mainly fund libraries. Information retrieval systems opened a gate in the walls of libraries by offering the access to outside resources. Indeed, the community of patrons remains limited and the sophistication of the tools clearly showed the need of information specialists. In the virtual library, the walls are down and its business model is shaken. We will illustrate these new issues by the changes for collections and for patrons.